THE EFFECT OF INTERACTIVE LISTENING STRATEGIES ON UNIVERSITY EFL STUDENTS’ INTERPRETIVE COMPREHENSION - Siti Aminah Hasibuan; Fatin Nadifa; Syahrial Pane (JEE (Journal of English Education), 2026)
Listening comprehension plays an important role in English as a Foreign Language (EFL) learning, particularly in helping students interpret meaning beyond literal understanding and engage effectively in communication. However, despite the increasing emphasis on interactive approaches in language pedagogy, many EFL classrooms still rely on traditional teacher-centered listening practices, creating a gap between theoretical perspectives and classroom implementation. This study examines the effect of interactive listening strategies on EFL students’ interpretive comprehension. A quasi-experimental design was employed involving an experimental group that received instruction through interactive listening strategies and a control group that received conventional instruction. Data were collected through pre-test and post-test instruments and analyzed using statistical procedures to identify differences between the two groups. The findings indicate that students taught through interactive listening strategies demonstrated better improvement in interpretive comprehension than those taught through conventional methods. These findings suggest that interactive listening strategies effectively support the development of higher-order listening skills. The study highlights the importance of integrating interactive and student-centered approaches into listening instruction to improve EFL students’ interpretive comprehension abilities.